Does Work Engagement Mediate the Effect of Polychronicity on Performance Outcomes? A Study in the Hospitality Industry in Northern Cyprus - Karatepe, Osman M.; Karadaş, Georgiana; Azar, Arezou Khabbaz; Naderiadib, Nazanin (My University, 2013)
The present study investigates work engagement as a mediating variable in the relationship between polychronicity and performance outcomes. Respondents were full-time frontline employees in the five-star hotels in the Turkish Republic of Northern Cyprus. The results from structural equation modeling reveal that the impact of polychronicity on job performance and extra-role customer service is fully mediated by work engagement. Theoretical and practical implications of the results are presented in the study. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Hotel employees; performance outcomes; polychronicity; Turkish Republic of Northern Cyprus; work engagement